1997
DOI: 10.3109/00048679709062676
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Experiences in Psychiatric Training. Part 2

Abstract: The high response rate of both trainees and consultants gives these results a level of representative validity. Recommendations in relation to future training and research are put forward. Specific training in the management of potentially assaultive patients and facilitating trainee recovery from assault or threat of assault should be a priority of the Royal Australian and New Zealand College of Psychiatrists. Support and education in relation to patient suicide is also important. Training and recognition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
84
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 20 publications
5
84
2
Order By: Relevance
“…In their questionnaire survey of consultant psychiatrists in Scotland, Alexander et al (2000) reported that 68% had a patient who committed suicide under their care. Looking at trainees in particular, for whom the impact of suicide may be greater, Dewar et al (2000) found that 47% had experienced the suicide of a patient and many trainees consider it one of the most adverse experiences of their training (Kozlowska et al, 1997). Similarly, Courtenay and Stephens (2001) report that 54% of their sample of trainees had a patient under their care who had committed suicide, a figure consistent with a rate of 0.23 suicides per training year.…”
Section: The Psychiatristmentioning
confidence: 97%
See 4 more Smart Citations
“…In their questionnaire survey of consultant psychiatrists in Scotland, Alexander et al (2000) reported that 68% had a patient who committed suicide under their care. Looking at trainees in particular, for whom the impact of suicide may be greater, Dewar et al (2000) found that 47% had experienced the suicide of a patient and many trainees consider it one of the most adverse experiences of their training (Kozlowska et al, 1997). Similarly, Courtenay and Stephens (2001) report that 54% of their sample of trainees had a patient under their care who had committed suicide, a figure consistent with a rate of 0.23 suicides per training year.…”
Section: The Psychiatristmentioning
confidence: 97%
“…Initially there are often feelings of shock or disbelief (Kozlowska et al, 1997), which may evolve into denial that the death has taken place or that the death was in fact suicide. Anger may become prominent and may be directed towards the deceased or his/her family (Jones, 1987).…”
Section: The Psychiatristmentioning
confidence: 99%
See 3 more Smart Citations